2019
DOI: 10.1002/jbio.201900017
|View full text |Cite
|
Sign up to set email alerts
|

Video‐assisted parathyroid gland mapping with autofocusing

Abstract: Preservation of the parathyroid gland (PTG) in neck endocrine surgery is important for regulating the amount of calcium in the blood and within the bones. Localization of the PTG has been attempted using various methods such as ultrasound, sestamibi, computerized tomography, magnetic resonance imaging and indocyanine green fluorescence imaging. These methods cannot be used during surgery, have high sensitivity or have PTG specificity. However, autofluorescence technique has shown high sensitivity and does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…With experience and proper calibration, NIRAF technologies enable earlier and improved PG identification compared with the current gold standard, the surgeon’s unaided eye . The NIRAF imaging can identify 90% to 100% of PGs with 90% to 100% sensitivity and accuracy . In one study, when compared concurrently in the same set of 20 patients, probe-based NIRAF was more sensitive in PG identification vs camera image–based NIRAF (detection rate of 97% and 91%, respectively) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With experience and proper calibration, NIRAF technologies enable earlier and improved PG identification compared with the current gold standard, the surgeon’s unaided eye . The NIRAF imaging can identify 90% to 100% of PGs with 90% to 100% sensitivity and accuracy . In one study, when compared concurrently in the same set of 20 patients, probe-based NIRAF was more sensitive in PG identification vs camera image–based NIRAF (detection rate of 97% and 91%, respectively) .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The NIRAF imaging can identify 90% to 100% of PGs 16,[18][19][20][21][22][23][24][25] with 90% to 100% sensitivity and accuracy. 16,21,24,[26][27][28] In one study, when compared concurrently in the same set of 20 patients, probe-based NIRAF was more sensitive in PG identification vs camera image-based NIRAF (detection rate of 97% and 91%, respectively). 19 A meta-analysis of 2062 patients found a 98% sensitivity and 99% specificity of NIRAF (probe or camera based) to identify PG during thyroid surgery.…”
Section: Comparison Of Probe-based and Camera-based Technologiesmentioning
confidence: 99%
“…Therefore, NIR‐AF is not a “one‐shot” procedure, but the surgeon can use it multiple times during the entire procedure whenever it is considered appropriate. Recently, some authors introduced the concept of “parathyroid mapping,” 20,42 or a systematic approach on PG identification with different steps: first stage images (P1) were obtained by the surgeon before dissection pointing the camera at predicted locations of PGs; the second stage (P2) was performed after the surgeon dissected or identified PGs with the naked eye not visualized in stage 1; third stage images (P3) were then taken from removed surgical specimens when PGs were not detected in stages P1 or P2.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al constructed an experimental setup based on a digital single-lens reflex camera with the aim of designing a PTG detection tool for thyroidectomies. They reached a PTG detection rate of 100% (n = 8) and 98.6% (n = 38) prior to surgical dissection with the system taking photographic images [97,104] and 98.1% with an improved autofocusing video-imaging system [105]. Feasibility studies on case series of parathyroidectomies found high (98.8%-100.0%) intraoperative PTG detection rates with different technical setups [98,106].…”
Section: Af Of the Thyroid And Parathyroid Glandsmentioning
confidence: 99%